Beyond the wrapping of the story: Angelica escaping and Angelica on the way in the "Orlando furioso" (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2024)
Traditionally interpreted as a fickle woman perpetually on the run, as a metaphor for the unattainability of desires and as a narrative cog that is deactivated once her function of triggering the madness of Orlando and the other knights has been exhausted, the figure of Angelica is also presented, in the Orlando furioso, as a character endowed from the outset with a specific desiring dimension. The essay therefore considers the dual status of Angelica, at once a woman-object exposed to the knights' concupiscence, gradually deprived of the possibility of moving, concealing her body and making autonomous decisions, and an individual who from the very beginning of the poem is, like the other characters, the holder of her own paradoxical inquiry: to leave the poem, and thus escape a narrative universe that condemns her to the role of prey and reward. The essay also examines the possible reception of this “double Angelica”, at once object and subject of desire, in the illustrations of the sixteenth-century editions of the poem.
Keywords: Ariosto; Orlando furioso; Angelica; Illustrated editions